A Study of Prevalence of Intestinal Protozoan Infections and Associated Risk Factors Among the School Children of Itahari, Eastern Region of Nepal - Sah, Ram Bilakshan; Paudel, IS; Baral, R; Poudel, P; Jha, N; Pokharel, PK (Journal of Chitwan Medical College, 2013)
Intestinal parasites, notably the protozoa are among the most common infections of school age children where they cause morbidity in developing countries.The objective of the study was to measure the prevalence of intestinal protozoan infection and to identify risk factors associated with protozoan infection among the school children of Itahari.The cross sectional study was conducted in Grade VI, VII and VIII in schools of Itahari Municipality. Stratified random sampling method was applied to choose the schools and the study subjects. Semi-structured questionnaire was administered to the study subjects and microscopic examination of stool was done.The Chi-square test was used to measure the association of risk factors and intestinal protozoan infections.Overall intestinal protozoan infection was found to be 18.5 percent. Giardia lamblia was found high (10.5%) in comparison to Entamoeba histolytica (8%). Almost (18.4%) of male and (18.6%) of female were infected with protozoan parasites. The use of soap and water after defecation had lower prevalence of protozoan infections (16%) than only use of water (28.9%). The protozoan infection was significantly lower among having clean nail (6%) in comparison to having not clean (24.8%) respectively. We conclude that the prevalence of intestinal protozoan infection was found to be high in school children of Itahari and those having unhygienic skin, nail and clothes, and the habit of nail biting and thumb sucking was found to have significant relationship in the causation of intestinal protozoan infection. Journal of Chitwan Medical College 2013; 3(1): 32-36 DOI: http://dx.doi.org/10.3126/jcmc.v3i1.8463